Gestational complications of the prothrombin G20210A mutation related to prothrombin activity - M. G. Nikolaeva; N. N. Yasafova; A. P. Momot; M. S. Zainulina; K. A. Momot; I. A. Taranenko (Акушерство, гинекология и репродукция, 2020)
Aim: to study the association between prothrombin activity in the blood plasma and gestational complications in women with the prothrombin G20210A mutation.Materials and methods. A prospective clinical cohort study including 290 pregnant women aged 18 to 45 years was conducted from 2012 to 2018. Two cohorts were formed: a study group of 140 patients with the GA genotype and a control group of 150 women with the GG genotype. In the groups, the activity of prothrombin (Factor II) in the venous blood plasma was evaluated during pregnancy. The stages of cytotrophoblast invasion were taken into account when relating the prothrombin activity to gestational complications.Results. The median prothrombin activity in the control group ranged from 108 % during the preconception period to 144 % during pregnancy (95 % CI = 130–150). In the study group with the GA genotype, the activity was significantly higher at the same periods: from 149 to 181 % (95 % CI = 142–195; p < 0.0001). With the prothrombin activity from 148.5 to 180.6 %, the pregnancy in the study group progressed normally. Higher levels of prothrombin activity were associated with early and/or severe preeclampsia (PE), and fetal growth retardation (FGR).Conclusion. The obtained data on prothrombin activity in the blood plasma during pregnancy complications suggest that the manifestation of the GA genotype in the form of early and/or severe PE and FGR is associated with the level of plasma prothrombin activity. The threshold value of Factor II activity was calculated for patients with the G20210A mutation; based on this value it becomes possible to predict PE at the preconception stage (171.0 %; AUC – 0.86; p < 0.0001) and at a gestational age of 7–8 weeks (181.3 %; AUC – 0.84; p < 0.0001).